The analysis of the influence of spironolactone and its combination with trimetazidine treatment on clinical symptoms, and cardiac structure and function parameters in chronic heart failure with preserved ejection fraction patients - Єна, Лариса Михайлівна; Ярош, Віталіна Олександрівна (ScienceRise: Medical Science, 2016)
Aim. To study clinical symptoms dynamics, functional condition, the quality of life, and cardiac structure and function in patients having chronic heart failure with preserved ejection fraction (CHFPEF) after Spironolactone (S) and its combination with Trimetazidine (S+T) therapy. Methods. 90 patients (aged from 60-74 years) suffering from hypertension with CHFPEF were examined using echocardiography, 6-minute walk test (SMWT), and the Minnesota living with heart failure questionnaire (MLHF) before, 6 and 12 months later after the standard therapy (K), standard with S use, and standard with S+T use. Results. On the clinical symptoms positive dynamics background, the distance of SMWT significantly increased on 26±9 m in К, 36±9 m in S, and 55±8 m in S+T; according to the MLHF, the number of points decreased: on 9,9±2,4, 17,1±2,6 і 12,9±2,3, respectively. A statistically significant decrease in left ventricular mass (LV) was on 10,4±4,4 g in К, 22,1±7,9 g in S, and 28,6±7,7g in S+T, but only in S and in S+T it accompanied by left atrium decrease – on 9,3±2,4 ml and 8,8±2,3 ml (p<0,05), respectively. The use of S and S+T led to the more expressed E/E reduction – on 2,3±0,8 cu and 2,8±0,5 cu (all р <0,05), respectively, comparing to K – on 1,2±0,4 cu (p>0,05). Systolic blood pressure (BP) in the pulmonary artery significantly decreased only in S and S+T. More distinct dynamics of echocardiographic parameters in case of S and S+T partly can be associated with more significant decrease in systolic and diastolic BP. Conclusion. Adding Spironolactone and its combination with Trimetazidine to the standard therapy of CHFPEF patients leads to the more significant functional condition positive dynamics, the quality of life, more expressed LV hypertrophy regression, system BP and BP in the pulmonary artery decrease, the improvement of LV diastolic functon